PENDATAAN ADMINISTRASI KEPENDUDUKAN OLEH PEMERINTAH KELURAHAN LIBUO KECAMATAN DUNGINGI KOTA GORONTALO - Lismawati; Nggilu, Rukiah; Antu, Yahya (stiatabalong.ac.id, 2024)
The administration of population is crucial for creating accurate and valid population data as a basis for policies and development programs. However, data collection in Libuo Village, Dungingi District, Gorontalo City is still done manually and has not been effective, The improvements are necessary for the quality and quantity of human resources as well as the utilization of technology. This study aims to investigate the population administration data collection by the Libuo Village Government in Dungingi District, Gorontalo City. The research method used is descriptive with a qualitative approach. The data sources used are primary data from research informants and secondary data. The number of informants in this study is 7, consisting of 5 village office employees and 2 community members. Data collection techniques include observation, interviews, and documentation. The data are analyzed by using data reduction, data presentation, and conclusion drawing techniques. The results of the study conclude that from the aspect of population administration data collection, employees are not effective and data collecting still manually. From the aspect of human resources, the employees conducting the population administration data collection are still limited. From the aspect of verification and validation, the population administration data collection conducted by the employees has not been optimal. Based on these findings, it is recommended to improve knowledge, insight, computer operation skills, and the number and quality of human resources conducting population administration data collection in Libuo Village, Dungingi District, Gorontalo City, and to provide training related to the use of advanced technology so that data collection can be carried out efficiently and accurately. Keywords: Data Collection ; Population Administration ; Governance